Mitochondrial biogenesis and genetics. - Attardi, Giuseppe; Chomyn, Anne (Methods in enzymology, 1995)
The critically acclaimed laboratory standard for forty years, Methods in Enzymology is one of the most highly respected publications in the field of biochemistry. Since 1955, each volume has been eagerlyawaited, frequently consulted, and praised by researchers and reviewers alike. More than 250 volumes have been published (all of them still in print) and much of the material is relevant even today--truly an essential publication for researchers in all fields of life sciences. Key Features * Structural and functional analysis of oxidative phosphorylation complexes * Import of proteins and RNA into mitochondria * Ion and metabolite transport systems in mitochondria * Biophysical methods for mitochondrial function analysis * Mitochondrial inheritance and turnover.